Safety and risks of CBD oils purchased online: unveiling uncertain quality and vague health claims - Vida, Róbert György; Strauss, Lilien Victoria; Bajtel, Ákos; Kiss, Tivadar; Csupor, Dezső; Fittler, András (Frontiers in Pharmacology, 2023)
The unmet need for highly effective, natural-derived products with minimal side effects results in the over-popularity of ever-newer medicinal plants. In the middle of 2010, products containing cannabidiol (CBD), one of the special metabolites of Cannabis sativa, started to gain popularity. For consumers and healthcare providers alike, the legal context surrounding the marketing of CBD products is not entirely clear, and the safety of using some products is in doubt. Companies in the online medicinal product market profit from the confusion around CBD oils. In our study, we employed a complex method known as risk-based safety mapping of the online pharmaceutical market, which included health claim content analysis of online stores, test purchases, labeling and quantitative analysis of CBD content. There were discovered 16 online retailers selling an average of 2 to 7 goods and CBD oils with a concentration of 3 to 5% (30 to 50 mg/ml) CBD. The majority (n/N =10/16, 62,5%) displayed potential health related benefits indirectly on their website and in case of one web shop (n/N =1/16, 6.3%) we detected COVID-19-related use. Altogether, 30 types of purported “indications” were collected. 12 CBD oil products were test purchased from online retailers in December 2020. Upon evaluating the packaging and product information we noticed that 3 products (n/N =3/12, 25%) lacked instructions on use, hence increasing the risk of inappropriate application and dosing. The cannabidiol content was quantified using UHPLC. The measured CBD concentrations of the products ranged from 19.58 mg/ml to 54.09 mg/ml (mean 35.51 mg/ml, median 30.63 mg/ml, SD ±12.57mg/ml). One (8.33%) product was under-labeled, five (41.67%) were over-labeled, and only every second product (50%) was appropriately labeled based on the quantitative assessment of CBD concentration. Further research and quality control is necessary to establish the regulatory context of the usage and classification of CBD and other cannabinoids in non-medicinal products (e.g.: food supplements), as authorities and policymakers around the world struggle with the uncertainties surrounding CBD products.